Effects of Tannic Acid on Lipid and Protein Oxidation, Color, and Volatiles of Raw and Cooked Chicken Breast Meat during Storage - Marwan Al-Hijazeen; Eun Joo Lee; Aubrey Mendonca; Dong Uk Ahn (MDPI AG, 2016)
The objective of this study was to determine the effect of tannic acid (TA) on the oxidative stability and the quality characteristics of ground chicken breast meat. Five treatments including (1) control (none added), (2) 2.5 ppm TA, (3) 5 ppm TA, (4) 10 ppm TA, and (5) 5 ppm butylated hydroxyanisole (BHA) were added to boneless, skinless ground chicken breast meat, and used for both raw and cooked meat studies. For the raw meat study, the ground chicken breast meat was packaged in oxygen-permeable bags and stored at 4 °C for 7 days. For the cooked study, raw ground meat samples were vacuum-packaged in oxygen-impermeable vacuum bags, cooked in-bag to the internal temperature of 75 °C, re-packaged in oxygen-permeable bags, and then stored. Both raw and cooked meats were analyzed for lipid and protein oxidation, color, and volatiles (cooked meat only) at 0, 3, and 7 days of storage. Raw meats with 10 ppm of TA added had significantly (p ≤ 0.05) lower lipid and protein oxidation than other treatments during storage. In addition, TA at 10 ppm level maintained the highest color a*- and L*-values during storage. Cooked chicken breast meat with 5 and 10 ppm TA added produced significantly (p ≤ 0.05) lower amounts of off-odor volatiles than other treatments. Among the volatile compounds, the amount of hexanal increased rapidly during storage for cooked meat. However, meats with 5 and 10 ppm TA added showed the lowest amount of hexanal and other aldehydes related to lipid oxidation, indicating a strong antioxidant effect of TA in cooked chicken breast meat. Furthermore, the differences in aldehydes among the treatments were bigger in cooked than in raw meat, indicating that the antioxidant effect of TA in cooked meat was greater than that in raw meat. Therefore, TA at >5 ppm can be used as a good natural preservative in cooked chicken meat to maintain its quality during storage.